Photoexcited state properties of carbon dots from thermally induced functionalization of carbon nanoparticles. Issue 44 (3rd November 2016) - Hu, Yin; Al Awak, Mohamad M.; Yang, Fan; Yan, Sijia; Xiong, Qingwu; Wang, Ping; Tang, Yongan; Yang, Liju; LeCroy, Gregory E.; Hou, Xiaofang; Bunker, Christopher E.; Xu, Linxi; et al.
Abstract : Carbon dots prepared by using a hybrid approach are demonstrated for their photoexcited state properties and bactericidal activities. Abstract : Carbon dots are small carbon nanoparticles with various surface passivation schemes, in which more effective has been the deliberate chemical functionalization of the nanoparticles for brighter fluorescence emissions, even though the synthesis method is more tedious and subject to some limitations in the selection of functionalization molecules. Another more popular synthesis method has been the carbonization of organic species, with the method being more efficient and versatile, but less controllable regarding synthesis and achieving the desired dot structure and performance. In this work, a hybrid approach combining the advantageous characteristics of the two synthesis methods was applied to the preparation of carbon dots using polyethyleneimine (PEI) for surface passivation, where pre-processed and selected small carbon nanoparticles were functionalized with PEI by microwave-induced thermal reactions. Their optical absorption and fluorescence emission properties were evaluated, and the results suggested that the carbon dots thus prepared shared the same photoexcited state characteristics with those from the deliberate chemical functionalization, including comparable fluorescence colors and other properties. A further demonstration of the similarity in photoexcited state properties was based on the same visible light-activated bactericidal functions of the PEI-carbon dots as those found in carbon dots from the deliberate chemical functionalization method. The advantages and potential limitations of the hybrid approach for more controllable yet versatile and efficient syntheses of carbon dots are highlighted and discussed.